Heart Rate Dynamics after Exercise in Cardiac Patients with and without Type 2 Diabetes - Kiviniemi, Antti M.; Hautala, Arto J.; Karjalainen, Jaana; Piira, Olli-Pekka; Catai, Aparecida M.; Mäkikallio, Timo H.; Huikuri, Heikki V.; Tulppo, Mikko P.; Neves, Victor R. (Frontiers in Physiology, 2011)
Purpose: The incidence of cardiovascular events is higher in coronary artery disease patients with type 2 diabetes (CAD+T2D) than in CAD patients without T2D. There is increasing evidence that the recovery phase after exercise is a vulnerable phase for various cardiovascular events. We hypothesized that autonomic regulation differs in CAD patients with and without T2D during post-exercise condition. Methods: A symptom-limited maximal exercise test on a bicycle ergometer was performed for 68 CAD+T2D patients (age 61 ± 5 years, 78% males, ejection fraction 67 ± 8, 100% on β-blockade) and 64 CAD patients (age 62 ± 5 years, 80% males, ejection fraction 64 ± 8, 100% on β-blockade). Heart rate (HR) recovery after exercise was calculated as the slope of HR during the first 60 sec after cessation of exercise (HRRslope). R-R intervals were measured before (5 min) and after exercise from 3 to 8 min, both in a supine position. R-R intervals were analyzed using time and frequency methods and a detrended fluctuation method (α1). Results: BMI was 30 ± 4 vs. 27 ± 3 kg•m2 (p < 0.001); maximal exercise capacity, 6.5 ± 1.7 vs. 7.7 ± 1.9 METs (p < 0.001); maximal HR, 128 ± 19 vs. 132 ± 18 bpm (p = ns); and HRRslope, -0.53 ± 0.17 vs. -0.62 ± 0.15 beats/sec (p = 0.004), for CAD patients with and without T2D, respectively. There was no differences between the groups in HRRslope after adjustment for METs, BMI and medication (ANCOVA, p = 0.228 for T2D and e.g. p = 0.030 for METs). CAD+T2D patients had a higher HR at rest than nondiabetic patients (57 ± 10 vs. 54 ± 6 bpm, p = 0.030), but no other differences were observed in HR dynamics at rest or in post-exercise condition. Conclusion: HR recovery is delayed in CAD+T2D patients, suggesting impairment of vagal activity and/or augmented sympathetic activity after exercise. Blunted HR recovery after exercise in diabetic patients compared with nondiabetic patients is more closely related to low exercise capacity and obesity than to T2D itself.